Operationalisation of a standardised scoring system to assess adherence to the World Cancer Research Fund/American Institute for Cancer Research cancer prevention recommendations in the UK biobank - Malcomson, Fiona C.; Parra-Soto, Solange; Lu, Liya; Ho, Frederick K.; Perez-Cornago, Aurora; Shams-White, Marissa M.; van Zutphen, Moniek; Kampman, Ellen; Winkels, Renate M.; Mitrou, Panagiota; Wiseman, Martin; Romaguera, Dora; et al. (Frontiers in Nutrition, 2023)
Introduction: In 2018, The World Cancer Research Fund (WCRF)/American Institute for Cancer Research (AICR) published ten evidence-based Cancer Prevention Recommendations designed to reduce the risk of cancer via improved lifestyle behaviours. In 2019, Shams-White and colleagues created the ‘2018 WCRF/AICR Score’ which aimed to standardise how adherence to these recommendations is assessed. The standardised scoring system includes seven of the recommendations concerning weight, physical activity and diet, with an optional eighth recommendation on breastfeeding. To promote transparency and reproducibility, the present paper describes the methodology for operationalisation of the standardised scoring system in the UK Biobank. Methods: UK Biobank recruited >500,000 individuals aged 37-73 years, between 2006 and 2010. In 2021, we held a workshop with experts which aimed to reach consensus on how to operationalise the scoring system using data available within UK Biobank. We used data on anthropometric measurements, physical activity and diet to calculate adherence scores. 24-hour dietary assessment data were used to measure adherence to the following recommendations: ‘Eat a diet rich in wholegrains, vegetables, fruit, and beans’, ‘Limit consumption of “fast foods” and other processed foods high in fat, starches or sugars’ and ‘Limit consumption of sugar-sweetened drinks’; food frequency questionnaire data were used to assess adherence to ‘Limit consumption of red and processed meat’ and ‘Limit alcohol consumption’. Participants were allocated points for meeting, partially meeting or not meeting each recommendation (maximum 1 point per recommendation), using cut-offs defined in the standardised scoring system. Results: At our workshop, discussions included the use of national guidelines to assess adherence to the recommendation on alcohol consumption, as well as challenges faced including defining the adapted ultra-processed food variables. A total score was calculated for 158,415 participants (mean 3.9 points, range 0 – 7 points). We also describe the methodology to derive a partial 5-point adherence score using data from the food frequency questionnaire in 314,616 participants. Discussion: We describe the methodology used to estimate adherence to the 2018 WCRF/AICR Cancer Prevention Recommendations for participants in the UK Biobank, including some of the challenges faced operationalising the standardised scoring system.